Sucesso, resistência e censura: amor e politização popular através da trajetória e obra de Odair José (década de 1970) - Sedano, Eder Aparecido Ferreira (2023)
The purpose of this Thesis is to recover and discuss the career and work of singer-songwriter Odair José, as well as the representations of everyday life and the popular sectors present in them. It is also intended to question the impact of the recording industry and censorship bodies on the artist's repertoire, as well as to problematize the forms of engagement and politicization in his production. At first, Odair's life trajectory, career, and artistic production will be researched, as well as the impact caused by repressive market and institutional trends, observing the representations of popular daily life contained therein (the experience of common subjects still little focused on by historiography, including domestic workers, prostitutes, children of separated parents, divorced women, homosexuals, among other social agents). For Odair, in narrating the daily lives of these protagonists, his activity as a composer resembled that of a musical narrator. The 1970s was a meteoric moment in his career when he established himself as one of the biggest record sellers in the country, but at the same time he was considered immoral and subversive by conservative sectors, and the military government's Censorship, and was among the most censored musicians of the period. In addition to the Censorship's tight grip, Odair had to face the prejudice of the intellectual elites, some artists, and the public of the MPB's (Popular Brazilian Music) engaged songs, who used the terms "tacky" and "corny" to inferiorize his production. Using a varied body of documentation, including censorship documents, song lyrics, and journalistic and oral sources, the purpose is to contribute to the development of the History and Music and History of Everyday Life fields of study, which are part of the broader framework of Cultural History. In addition, the purpose is to contribute to the process of decentralization of historical individuals, recovering the everyday life experiences of excluded and marginalized popular sectors